Integrated reporting and value creation: evidence from Malaysian companies / Shafawati Farhana Mohd Safihie - Mohd Safihie, Shafawati Farhana (2015)
Increasing pressure from stakeholders that demands for more transparency and accountability in companies' corporate reporting both in terms of financial and nonfinancial reporting, has resulted in a move towards a more integrated approach in corporate reporting to include the disclosure of both financial and non-financial information. Therefore, the use of Integrated Reports is seen as a critical move towards the integration of financial and non-financial information as it takes into consideration the economic, social and environmental factors. It is also expected that Integrated Reporting will create value to the organization. The aim of this study is to examine the presence of integrated reporting elements among Malaysian companies as integrated reporting is still voluntary in nature in Malaysia. The internal and external forces that drive companies to embark on integrated reporting in the context of agency and stakeholder theory were investigated including the subsequent effect of such reporting in creating value to the organizations. The sample for the study consists of the top 100 companies in Malaysia for the year 2014 as larger firms are expected to have more incentives and resources to embark on such reporting. Content analyses of the annual reports were undertaken to measure the presence of the elements of integrated reporting among the sample companies. The results of this study revealed that in terms of the dimensions of Integrated Reporting elements, the Assurance dimension had the highest disclosure score suggesting that management placed importance on the provision of credible information. The results of the multiple regression analysis revealed that mission and vision, and risk and opportunities had a positive and significant relationship with the elements of integrated reporting. The results of the study also revealed that the presence of Integrated Reporting elements in companies' annual report creates value to the organizations.